Clarifying the link between traumatic brain injury and homelessness: Workshop proceedings. (December 2013) - Topolovec-Vranic, Jane; Ennis, Naomi; Ouchterlony, Donna; Cusimano, Michael D.; Colantonio, Angela; Hwang, Stephen W.; Kontos, Pia; Stergiopoulos, Vicky; Brenner, Lisa
Abstract Purpose: To disseminate the proceedings of a 1-day multidisciplinary stakeholder workshop aimed at examining the inter-relationship between traumatic brain injury (TBI) and homelessness. Methods: Thirty-seven stakeholders participated in the workshop, including frontline workers with individuals who are homeless, physicians, nurses and other healthcare workers, researchers, policy-makers, students and individuals with lived experience of homelessness. Didactic presentations, large group discussions and break-out sessions were used to disseminate knowledge, identify service and research gaps, develop a research agenda and facilitate networking. Results: The participants identified barriers to service provision for individuals who are homeless and have sustained TBI with a focus on age- and gender-related issues, co-morbid TBI and mental illness and jurisdictional differences. Challenges and strategies related to engaging stakeholders in research with this population, as well as disseminating knowledge were discussed and research questions were identified. Conclusion: There is very little empirical literature on the topic of TBI and homelessness. The workshop identified key issues for consideration, including gaps in knowledge related to this topic.